2004
DOI: 10.1097/00002060-200406000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Functioning with Same-Hospital Readmission After Stroke

Abstract: The importance of physical functioning goes beyond rehabilitation. It is a potentially modifiable variable with implications for readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 13 publications
3
30
0
Order By: Relevance
“…Most likely, this is because the patients discharged to the nursing homes had more disabling strokes. As in our hospital based study, severe strokes and increased functional disability have consistently been shown to predict readmission in administrative databases [8,22]. Another plausible explanation is that caregivers at home and in acute care-rehabilitation settings are able to pick up problems earlier and can address issues before they become serious to require hospitalization.…”
Section: Discussionsupporting
confidence: 52%
“…Most likely, this is because the patients discharged to the nursing homes had more disabling strokes. As in our hospital based study, severe strokes and increased functional disability have consistently been shown to predict readmission in administrative databases [8,22]. Another plausible explanation is that caregivers at home and in acute care-rehabilitation settings are able to pick up problems earlier and can address issues before they become serious to require hospitalization.…”
Section: Discussionsupporting
confidence: 52%
“…7,44 In the acute care setting, for example, Coleman et al 7 reported that including functional status based on survey data improved the prediction of readmissions compared with the use of administrative data alone in Medicare beneficiaries. Bohannon and Lee 6 also found that in patients with acute ischemic stroke, functional measures were predictive of readmissions independent of other demographic and clinical factors. In the context of inpatient rehabilitation, studies have separately evaluated read-missions that occurred during CIIRP and post-CIIRP discharge.…”
Section: Discussionmentioning
confidence: 91%
“…Over time, this results in a loss of the recovered gains achieved from rehabilitation, and sedentary behavior worsens physical function. This may have some relationship to the aforementioned high rates of rehospitalization in some populations [30,31]. Additionally, as a person with a disability remains inactive, physical deconditioning occurs that worsens and increases the risk of secondary conditions.…”
Section: Difficult Transition From Patient To Participantmentioning
confidence: 99%